Improving the Osteoblast Cell Adhesion on Electron Beam Controlled TiO2 Nanotubes. (28th May 2014) - Yoon, Sung Wook; Shim, Hyun Ju; Shim, In-Bo
Abstract : Here we investigate the osteogenesis and synostosis processes on the surface-modified TiO2 nanotubes via electron beam irradiation. The TiO2 nanotubes studied were synthesized by anodization process under different anodizing voltage. For the anodization voltage of 15, 20, and 25 V, TiO2 nanotubes with diameters of 59, 82, and 105 nm and length of 115, 276, and 310 nm were obtained, respectively. MC3T3-E1 osteoblast cell line was incubated on the TiO2 nanotubes to monitor the change in the cell adhesion before and after the electron beam irradiation. We observe that the electron beam irradiation affects the number of surviving osteoblast cells as well as the cultivation time. In particular, the high adhesion rate of 155% was obtained when the osteoblast cells were cultivated for 2 hours on the TiO2 nanotube, anodized under 20 V, and irradiated with 5, 000 kGy of electron beam.